Free-Breathing Inner-Volume Black-Blood Imaging of the Human Heart Using Two-dimensionally Selective Local Excitation at 3T - Abd-Elmoniem, Khaled Z. (2011)
Black-blood fast spin-echo imaging is a powerful technique for the evaluation of cardiac anatomy. To avoid fold-over artifacts, using a sufficiently large field of view in phase-encoding direction is mandatory. The related oversampling affects scanning time and respiratory chest motion artifacts are commonly observed. The excitation of a volume that exclusively includes the heart without its surrounding structures may help to improve scan efficiency and minimize motion artifacts. Therefore, and by building on previously reported inner-volume approach, the combination of a black-blood FSE sequence with a two-dimensionally selective radiofrequency pulse is proposed for selective “local excitation” small-FOV imaging of the heart. This local excitation technique has been developed, implemented, and tested in phantoms and in vivo. With this method, small-FOV imaging of a user-specified region in the human thorax is feasible, scanning becomes more time efficient, motion artifacts can be minimized and additional flexibility in the choice of imaging parameters can be exploited.